Integration of Islamic Religious Education and Modern Economics: Revitalizing The Four Prophet Muhammad’s Character Pillars As A Role Model For Mu’amalah Practices Among Gen-Z - Ramadhan, Sayid Ahmad; Normuslim; Hamdanah (International Journal of Social Science and Religion (IJSSR), 2025)
This study aims to critically examine the synergy between Islamic Religious Education (PAI) and the modern economy through the revitalization of the four prophetic traits of Prophet Muhammad PBUH namely is shiddiq, amanah, tabligh, and fathanah, as an alternative approach to shaping the economic character of Generation Z. The research was conducted using a library research method by reviewing various relevant literature to develop a transformative and applicable educational model. The findings indicate an urgent need to redesign PAI learning so that it becomes more adaptive to technological advancements and capable of fostering active student engagement in understanding socio-economic dynamics. Furthermore, the contribution of this revitalization in the PAI learning system should be thoroughly formulated and implemented to produce a generation that is not only spiritually devout but also competent, possesses integrity, and is committed to social justice and sustainability. On the other hand, there are several foundational tasks that must be addressed prior to its realization. These include the need for curriculum enhancement programs, increased professionalism among all educational components, and the development of an integrative evaluation system to help establish a dignified Islamic economic system.